Study on the Diffusion Law of Fluidized Filling Gangue Slurry in Goaf of Coal Mine Underground - Baoning Wei; Qingxiang Huang; Dengdeng Zhuang; Xin Cao; Bo Hui; Xiao Zuo; Mengbo Zhu (Geofluids)
In response to the challenge posed by the limited capacity of postmining paste and original waste filling mining technology for small-scale waste rock treatment, which is incompatible with the requirements of modern high-yield mines producing millions of tons, fluidized filling mining technology in goaf presents a sustainable and environmentally friendly solution. This innovative method effectively addresses the balance between mining and filling operations while enabling large-scale waste rock management in coal mines. This article presents a model for predicting the spatial morphology of goaf and employs theoretical calculations to determine the residual space left after goaf caving. It unveils the fluidization filling approach for goaf caving, utilizing a “high- and low-level collaborative filling” strategy and taking advantage of various types of residual spaces within cavities and voids. Experimental investigations into gangue slurry diffusion in the goaf reveal insights into its diffusion patterns along three directions: horizontal, inclined, and vertical. The analysis also establishes correlations between porosity, space utilization rate, and the Talbol index. Furthermore, the research identifies the flow characteristics of fluidized filling slurry as consistent with the Bingham fluid behavior. A calculation formula for determining the diffusion radius of the filling slurry within cracks is provided. The study highlights four distinct flow stages in the process: stable laminar diffusion, transition from advection to turbulence, turbulence, and stoppage. To validate these findings, COMSOL simulation software is employed to simulate and analyze the diffusion patterns of gangue slurry within the goaf. The research outcomes offer valuable theoretical insights into the postgangue fluidization goaf filling technology and serve as a technical reference for the design of coal-based solid waste fluidization filling processes.